Search for long-lived charged massive particles in pp collisions at square root s = 1.8 TeV. - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2003)
We report a search for the production of long-lived charged massive particles in a data sample of 90 pb(-1) of square root[s]=1.8 TeV pp collisions recorded by the Collider Detector at Fermilab. The search uses the muonlike penetration and anomalously high ionization energy loss signature expected for such a particle to discriminate it from backgrounds. The data are found to agree with background expectations, and cross section limits of O(1) pb are derived using two reference models, a stable quark and a stable scalar lepton.